2018
DOI: 10.4269/ajtmh.18-0109
|View full text |Cite
|
Sign up to set email alerts
|

New Evidence of the Monophyletic Relationship of the Genus Psammolestes Bergroth, 1911 (Hemiptera, Reduviidae, Triatominae)

Abstract: The genus Psammolestes within the subfamily Triatominae and tribe Rhodniini comprises the species Psammolestes arthuri, Psammolestes coreodes, and Psammolestes tertius, all potential vectors of Chagas disease. A feature of Psammolestes is their close association with birds, which makes them an interesting model for evolutionary studies. We analyzed cytogenetically Psammolestes spp., with the aim of contributing to the genetic and evolutionary knowledge of these vectors. All species of the Psammolestes showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The distribution of species included in genus Psammolestes is restricted to Latin America, with P. coreodes being reported in Argentina, Bolivia, Brazil and Paraguay, P. tertius in Brazil and Peru and P. arthuri in Colombia and Venezuela [ 12 , 13 ]. Phylogenetic and cytogenetic analyses suggest that this genus is monophyletic [ 14 , 15 ]. Monteiro et al [ 14 ] suggested that perhaps Psammolestes should be regarded as a specialized lineage of Rhodnius from the prolixus group because the genus Psammolestes and species of the prolixus group share a common ancestral form, which highlights the paraphyly of the genus Rhodnius .…”
Section: Introductionmentioning
confidence: 99%
“…The distribution of species included in genus Psammolestes is restricted to Latin America, with P. coreodes being reported in Argentina, Bolivia, Brazil and Paraguay, P. tertius in Brazil and Peru and P. arthuri in Colombia and Venezuela [ 12 , 13 ]. Phylogenetic and cytogenetic analyses suggest that this genus is monophyletic [ 14 , 15 ]. Monteiro et al [ 14 ] suggested that perhaps Psammolestes should be regarded as a specialized lineage of Rhodnius from the prolixus group because the genus Psammolestes and species of the prolixus group share a common ancestral form, which highlights the paraphyly of the genus Rhodnius .…”
Section: Introductionmentioning
confidence: 99%
“…The frequencies of cytotypes varied in relation to the ecological and geographical characteristics of collection sites. Additionally, the cytotypes were consistent with morphological differences in size, morphometry of the wings and characters of the head [92,99]. Finally, cytogenetic characteristics (number and size of chromosomes, autosomal heterochromatin, and sex chromosomes) have also been used to evaluate intraspecific variability of different populations of R. prolixus and R. neglectus and no variation in cytotypes was observed with respect to the ecological and geographical characteristics of the populations analyzed [100].…”
Section: Cytogenetic Studiesmentioning
confidence: 55%
“…The genus Psammolestes has a close association with the nests of some species of birds belonging to the families Dendrocolaptidae, Troglodytidae, Furnariidae, and Icteridae 3 , 4 , 5 , 6 . This close association suggests that birds are their only source of food 2 , 7 .…”
mentioning
confidence: 92%
“…The genus Psammolestes comprises three species and seems to be specialized in exploiting bird-nest ecotopes 2 . Phylogenetic analyses of P. tertius and P. coreodes suggest that this genus is monophyletic and can be considered a specialized lineage of the Rhodnius prolixus group because they share a common ancestor, which in turn highlights the paraphyly of the genus Rhodnius 7,15 . Based on a projection of its potential geographic distribution, P. tertius presents intermediate climatological limits and occurs at the highest altitudes compared to the other species of the genus 12 .…”
mentioning
confidence: 99%